Performance Monitoring and Knowledge Worker Productivity - Muneer, Al Dwaikat; Kartinah, Ayupp; Yousef, Ahmad Alolabi (Human Resource Management Academic Research Society, 2022)
This study aims at developing a conceptual model depicting the interrelationship of employee performance monitoring, stress, knowledge management, and knowledge worker productivity. In this study, past research related to employee performance monitoring and knowledge worker productivity is used as base research to identify the study's constructs and develop the conceptual model. The final emerges model, which may be tested quantitatively, has four constructs. These are employee performance monitoring, stress, knowledge management, and knowledge worker productivity. In the finally evolved model, employee performance monitoring acts as the exogenous variable, knowledge worker productivity as the endogenous variable, and stress and knowledge management as mediators.